Efektivitas Penggunaan Modul Berbasis Differentiated Instruction untuk Meningkatkan Kemampuan Pemahaman Konsep Matematika Mahasiswa - Triana Harmini (Didaktik Matematika, 2019)
Teaching material is an essential component of learning. Teaching materials for Calculus courses, especially for the Department of Informatics, remains limited and orients towards a collection of materials and questions that cannot overcome the differences in student characteristics. Therefore, in the form of learning modules that can accommodate variations in student characteristics is a crucial need in teaching material. In this study, the learning module based differentiated instruction was compiled by taking into account the different characteristics of student ability levels. This study aimed to determine the effectiveness of Calculus learning by using learning modules based on differentiated instruction to students' conceptual understanding of the material of qualities and inequalities of absolute value. This research was experimental research and the subjects were the Informatics Engineering students of the University of Darussalam Gontor, enrolled in the first semester in the academic year 2018-2019. The research instrument was tests of conceptual understanding consisting of short-answer problems given at the beginning and the end of learning. The design of this study used One-Group Pretest-Postest Design and data analysis involved a Wilcoxon test due to the small number of subjects (25 people). The results of the analysis showed that the use of the learning modules based on differentiated instruction effectively enhanced the mathematical conceptual understanding of students.